Gut Microbiota: A Novel Regulator of Cardiovascular Disease and Key Factor in the Therapeutic Effects of Flavonoids - Li, Qinyu; Gao, Bing; Siqin, Bateer; He, Qian; Zhang, Ru; Meng, Xiangxi; Zhang, Naiheng; Zhang, Na; Li, Minhui (Frontiers in Pharmacology, 2021)
Cardiovascular disease is the main cause of death worldwide, and traditional cardiovascular risk factors cannot fully explain the occurrence of the disease. In recent years, the relationship between gut microbiota and its metabolites and cardiovascular disease has been a hot study topic. The changes in gut microbiota and its metabolites are related to the occurrence and development of atherosclerosis, myocardial infarction, heart failure, and hypertension. The mechanisms by which gut microbiota and its metabolites influence cardiovascular disease have been reported, although not comprehensively. Additionally, following ingestion, flavonoids are decomposed into phenolic acids that are more easily absorbed by the body after being processed by enzymes produced by intestinal microorganisms, which increases flavonoid bioavailability and activity, consequently affecting the onset of cardiovascular disease. However, flavonoids can also inhibit the growth of harmful microorganisms, promote the proliferation of beneficial microorganisms, and maintain the balance of gut microbiota. Hence, it is important to study the relationship between gut microbiota and flavonoids to elucidate the protective effects of flavonoids in cardiovascular diseases. This article will review the role and mechanism of gut microbiota and its metabolites in the occurrence and development of atherosclerosis, myocardial infarction, heart failure, and hypertension. It also discusses the potential value of flavonoids in the prevention and treatment of cardiovascular disease following their transformation through gut microbiota metabolism.